The devil is coming: Feeding behavior of juvenile Munk’s devil rays (Mobula munkiana) in very shallow waters of Punta Descartes, Costa Rica - Porsiel, Nathalie; Hernández, Sebastián; Cordier, Damien; Heidemeyer, Maike (Revista de Biología Tropical, 2021)
Introduction: Identifying critical habitats for vulnerable elasmobranch species is crucial for effective conservation measures. The Munk’s devil ray (Mobula munkiana) is endemic to the Eastern Pacific, but yet little is known about its biology, ecology, and habitat use. As filter feeders, it is assumed that this species concentrates at high-productive upwelling regions, such as the Costa Rican Dome. Like many elasmobranchs, its populations are highly depleted and require urgent information to inform better conservation measures. Objective: The study was conducted to gain information on a unique behavior observed in juvenile M. munkiana, so further information can be provided on early life stages of this vulnerable species. Methods: From June to September 2017 and in August 2018, the feeding behavior of juvenile Mobula munkiana was observed in two shallow bays located at Punta Descartes, North Pacific Costa Rica. Individuals were captured using a non-lethal method to obtain data on size, weight, and sex distribution. Plankton samples (n = 100) were taken at both bays throughout the months to infer diet composition. Results: Munk’s devil rays showed a repetitive swimming movement parallel to the beach, feeding exclusively in the shallow breaking zone of the low tide waves at depth <50cm. A total of 12 M. munkiana (11 live and one found dead) indicated a juvenile feeding aggregation ranging from 490 – 610mm in disk width and 1400 – 2300gr in weight. The sex ratio (males to females) was 3:1. Zooplankton of the order Mysidacae was found in the highest abundance in the breaking zone. Conclusions: The specific behavior and seasonal occurrence of juvenile Munk’s devil rays in this area seem to be driven by prey abundance. More research is needed to conclude the presence of reproductive adults at deeper depths and the year-round habitat use of Punta Descartes. The area is threatened by unsustainable development and requires realistic management strategies to guarantee the survival of vulnerable species and their critical habitats.